2004
DOI: 10.1165/rcmb.2003-0013oc
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma-Derived Growth Factor Is Involved in Lung Remodeling by Stimulating Epithelial Growth

Abstract: Lung epithelial cells have an integral role in the maintenance of lung homeostasis; however, the regulatory mechanism thereof has not been fully clarified. Recently, hepatoma-derived growth factor (HDGF) was reported to be involved in organ development and remodeling through its mitogenic effect. We investigated the biological role of HDGF in lung remodeling. HDGF was more highly expressed in the lungs of idiopathic pulmonary fibrosis, chiefly in the epithelial cells, than in control nonfibrotic lungs. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Although HDGF can stimulate DNA synthesis and cell proliferation in vascular or bronchial epithelial cells has been previously reported (8,9,13), our results are consistent with our clinical observation that the expression levels of HDGF was not associated with Ki67 labeling indices in primary NSCLC (10). In fact, HDGFmediated cell growth was observed only when the cells were cultured in serum-free condition (13,14); the presence of serum would have masked HDGF stimulation because of the effect of other growth stimulators in serum.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Although HDGF can stimulate DNA synthesis and cell proliferation in vascular or bronchial epithelial cells has been previously reported (8,9,13), our results are consistent with our clinical observation that the expression levels of HDGF was not associated with Ki67 labeling indices in primary NSCLC (10). In fact, HDGFmediated cell growth was observed only when the cells were cultured in serum-free condition (13,14); the presence of serum would have masked HDGF stimulation because of the effect of other growth stimulators in serum.…”
Section: Resultssupporting
confidence: 91%
“…In fact, HDGFmediated cell growth was observed only when the cells were cultured in serum-free condition (13,14); the presence of serum would have masked HDGF stimulation because of the effect of other growth stimulators in serum.…”
Section: Resultsmentioning
confidence: 99%
“…HDGF has been reported to be highly expressed in fetal tissues, and an association with the aggressive biological potential of cancer cells, such as proliferation, has been proposed (5,6,11,12). Whether cell growth arrest resulted in a decrease in HDGF expression was, therefore, tested.…”
Section: P53 Family Downregulates Expression Of the Hdgf Mrna And Promentioning
confidence: 99%
“…HDGF stimulates the proliferation of fibroblasts, endothelial cells, vascular smooth muscle cells, and some liver cancer cells. Recent studies have suggested the involvement of HDGF in the development of the liver, lung, kidney, gut, and cardiovascular systems (5)(6)(7)(8)(9). HDGF expression is increased in several types of carcinomas compared with adjacent nontumorous areas in mouse and human (10).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the length and amino acid sequences of carboxyl-terminal regions of HRPs vary considerably, suggesting a modular structure of these proteins, which is supported by NMR data analysis of human HDGF (10). Expression of HDGF mRNA as well as protein is developmentally regulated, and various results point to an important function of HDGF during tissue development, protection, and repair (6,(11)(12)(13)(14)(15)(16)(17)(18). In addition, studies on different types of cancers suggest a possible role of this growth factor in cancer development and neovascularization (19 -24).…”
mentioning
confidence: 91%